MODEL PEMBELAJARAN KOOPERATIF PADA MATERI PEMBELAJARAN SEPAK BOLA DI SMA SANTUN UNTAN - Sutrisno, Gebi; Atiq, Ahmad; Haetami, Mimi (Universitas Tanjungpura, 2022)
AbstractThe cooperative model is one of the models that is always used as a solution in the learning process, both for students and the teacher itself, so the role and application of cooperative models will become new knowledge for students. At the time of learning soccer material, the problem in this study was that the level of the cooperative model was able to be applied to students when learning soccer at the level of basic soccer technical skills that were SMA Santun Untan. The research method used is a survey method, with a percentage level of the cooperative model in physical education learning, consisting of several indicators and test items. The results showed that there was a level of cooperative model in the soccer material by answering yes 2,149 with a percentage of yes 75%, and 414 with a category of no with a percentage of 2.5%. This means that 100% of the understanding of the cooperative model of soccer material is absorbed very well and can be used as a vehicle for the next step. From the conclusions, the right advice is the need for knowledge of students to understand the cooperative model so that in the learning process they are able to develop themselves as knowledge insights and applications in the field, especially soccer material. Teachers and students must be able to work together in order to explore and provide mutual reinforcement during learning, according to the needs to be given during learning.Keywords : cooperative learning model in football learning materials